Tolerance mechanisms in allergen immunotherapy. Issue 6 (December 2020) - Celebi Sözener, Zeynep; Mungan, Dilsad; Cevhertas, Lacin; Ogulur, Ismail; Akdis, Mübeccel; Akdis, Cezmi
Abstract : Purpose of review: Allergen immunotherapy is the only treatment modality which alters the natural course of allergic diseases by restoring immune tolerance against allergens. Deeper understanding of tolerance mechanisms will lead to the development of new vaccines, which target immune responses and promote tolerance. Recent findings: Successful allergen immunotherapy (AIT) induces allergen-specific peripheral tolerance, characterized mainly by the generation of allergen-specific Treg cells and reduction of Th2 cells. At the early phase, AIT leads to a decrease in the activity and degranulation of mast cells and basophils and a decrease in inflammatory responses of eosinophils in inflamed tissues. Treg cells show their effects by secreting inhibitory cytokines including interleukin (IL)-10, transforming growth factor-β, interfering with cellular metabolisms, suppressing antigen presenting cells and innate lymphoid cells (ILCs) and by cytolysis. AIT induces the development of regulatory B cells producing IL-10 and B cells expressing allergen-specific IgG4. Recent investigations have demonstrated that AIT is also associated with the formation of ILC2reg and DCreg cells which contribute to tolerance induction. Summary: Research done so far, has shown that multiple molecular and cellular factors are dysregulated in allergic diseases and modified by AIT. Studies should now focus on finding the best target and ideal biomarkers to identify ideal candidates for AIT.